Public Perspectives on The “Lapor Mas Wapres” Program on The Indonesian Lawyers Club YouTube Channel - Bella Putri Nur Habibah; Dyva Claretta (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2025)
The transformation of information technology has created a new public space in digital media, which also serves as a political discourse arena. The